Iron deficiency and child psychomotor development in a rural region of Chota, Peru, 2022 - Rodrigo-Barboza, Sandi Analí; Bustamante-Tapia, Yuleysi; Oblitas Gonzales, Anibal (Universidad y Salud, 2023)
Introduction: Iron deficiency and psychomotor developmental delay are two public health problems that cause high childhood morbidity and mortality worldwide, which can be related to social, economic, cultural and health factors that affect the environment where children and their family live. Objective: To determine the relationship between iron deficiency anemia and psychomotor development in children aged 2 to 4 years treated at the Cuyumalca Clinic, Chota. Materials and methods: Relational, cross-sectional study conducted on 48 children, who underwent hemoglobin testing through a portable hemoglobinometer and were subjected to the Psychomotor Development Test. Results: 31.2% of the children displayed some type of anemia, with the most common being moderate anemia (17.7%). On average, 10.9% showed some type of psychomotor developmental delay, including coordination (6.3%), language (8.4%), motor skills (16.7%), and overall development (12.5%). 4.2% of the children who had minor to moderate anemia showed developmental delay risks in the three assessed areas as well as in their overall development. Conclusion: There is no statistically significant relationship between iron deficiency anemia and several domains of psychomotor development, including coordination, language, motor skills as well as overall development.